Perspectives on behavioural interventions in palliative and end-of-life care - Allen, Rebecca S.; Carpenter, Brian D.; Eichorst, Morgan K. (Aging and mental health research, 2018)
The challenges faced by individuals and families at the end of life are still incredibly diverse, and many behavioural interventions and clinical approaches have been developed to address this great diversity of experiences in the face of dying and death, helping providers to care for their clients. Perspectives on Behavioural Interventions in Palliative and End-of-Life Care is an accessible resource that collates and explores interventions that can be used to address a wide range of behavioural, psychological, social and spiritual issues that arise when people are facing advanced chronic or life-limiting illness. Dignity TherapyInterventions to enhance communication and decision makingInterventions embracing cultural diversity and intersectionality. Meaning-Centred Psychotherapy for cancer patientsThe management of physical and mental health symptomsTogether with Perspectives on Palliative and End-of-Life Care: Disease, Social and Cultural Context, the book provides a foundation for collaborative international and interprofessional work by providing state-of science information on behavioural interventions addressing mental health and wellness. It is of interest to academics, researchers and postgraduates in the fields of mental health, medicine, psychology and social work, and is essential reading for healthcare providers and trainees from psychosocial and palliative medicine, social work and nursing. With perspectives from experienced clinicians, providers, and caregivers from around the world, this book offers a strong foundation in contemporary evidence-based practice alongside seasoned practice insights from the field